Sealing material and insulating glass using the same

A sealing material composed of butyl-based rubber and inorganic fillers, with specific mass ratios, addresses the fire resistance challenges of double-layer glass, particularly with resin spacers, by enhancing fire prevention and durability, enabling compliance with the ISO834-1:1999 standard.

JP7666103B2Active Publication Date: 2025-04-22AGC INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021075286
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-28
Filing Date
2021-04-27
Publication Date
2025-04-22
Estimated Expiration
2041-04-27

Smart Images

  • Figure 0007666103000002
    Figure 0007666103000002
  • Figure 0007666103000003
    Figure 0007666103000003
  • Figure 0007666103000004
    Figure 0007666103000004
Patent Text Reader

Abstract

To provide a seal material for multiple glass having excellent fire resistance performance and a multiple glass using the same.SOLUTION: A sealing material characterized in that the sealing material that seals the peripheral edge of a multiple glass in which two or larger glass plates are disposed opposite to each other by separating through a spacer so as to form a hollow layer between them, in which the ratio of butyl rubber to the total amount of butyl rubber and crystalline polyolefin is 98 mass% or larger to 100 mass% or smaller, and the ratio of crystalline polyolefin is 0 mass% or larger and 2 mass% or smaller (including when crystalline polyolefin is not included), the ratio of the inorganic filler relative to a total 100 pts.mass of butyl rubber and crystalline polyolefin is 100 pts.mass or larger and 250 pts.mass or smaller.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealing material and insulating glass using the same. [Background technology]

[0002] Conventionally, in a double-glazing unit having two or more glass sheets arranged facing each other and separated only by a spacer so as to form a hollow layer between them, the spacer is made of a thermoplastic resin composition having a JIS A hardness of 10 to 90 at 25°C, the thermoplastic resin composition contains a butyl-based rubber, a crystalline polyolefin, a desiccant and an inorganic filler, the proportion of the butyl-based rubber relative to the total amount of the butyl-based rubber and the crystalline polyolefin is 50 to 98% by weight, the proportion of the crystalline polyolefin is 2 to 50% by weight, and the proportion of the inorganic filler is 200 parts by weight or less relative to 100 parts by weight of the total of the butyl-based rubber and the crystalline polyolefin is known (see, for example, Patent Document 1).

[0003] Patent Document 1 also discloses in its Figure 4 a double-glazing unit in which a hollow layer is isolated from the outside air by interposing a primary sealant 3 between glass plates 1a, 1b and a metal spacer 2, and a gap (recess) between the inner surfaces of the peripheries of the opposing glass plates and the outer peripheral surface of the spacer is sealed with a secondary sealant of room temperature setting, typically a polysulfide-based or silicone-based type. Patent Document 1 also discloses in its Figure 5 a double-glazing unit in which a resin mixed with a desiccant is used as a spacer 4, and the spacer is sealed with a secondary sealant of room temperature setting. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 10-114551 Summary of the Invention [Problem to be solved by the invention]

[0005] Various standards have been established to guarantee the quality of insulating glass. When insulating glass is used as fire-resistant insulating glass for fire protection, it is required to pass a fire resistance test based on ISO834-1:1999, which is a standard regarding durability in the event of a fire.

[0006] Such fire resistance tests are conducted by directing a flame from a burner at the front of the insulating glass for a specified time, and the glass is required to withstand the specified time without the flame penetrating the insulating glass and without collapsing. Here, whether or not the insulating glass collapses depends heavily on the fire resistance of the sealant (hereinafter also referred to as the "secondary sealant") that seals the peripheral part of the insulating glass.

[0007] Therefore, an object of the present invention is to provide a sealing material for insulating glass having excellent fire resistance, and insulating glass using the same. [Means for solving the problem]

[0008] In order to achieve the above object, a sealing material according to one aspect of the present invention is a sealing material for sealing a peripheral portion of insulating glass in which two or more glass plates are arranged opposite each other and spaced apart via a spacer so as to form a hollow layer therebetween, the sealing material comprising: The sealing material has a butyl-based rubber and an inorganic filler, the proportion of the butyl-based rubber relative to the total amount of the butyl-based rubber and the crystalline polyolefin is 98% by mass or more and 100% by mass or less, and the proportion of the crystalline polyolefin is 0% by mass or more and less than 2% by mass (including the case where the crystalline polyolefin is not included), The proportion of the inorganic filler relative to 100 parts by mass in total of the butyl-based rubber and the crystalline polyolefin is 100 parts by mass or more and 250 parts by mass or less. Effect of the Invention

[0009] According to the present invention, it is possible to provide a sealing material for insulating glass having high fire resistance, and insulating glass using the same. [Brief description of the drawings]

[0010] [Figure 1] 1 is a diagram showing a secondary sealing material and insulating glass according to a first embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram showing an example of a double glazing according to a first embodiment of the present invention, which is constructed using fire-resistant glass and Low-E glass. [Diagram 3] FIG. 1 is a diagram for explaining a fire resistance test method based on ISO834-1:1999. [Figure 4] FIG. 4 is a front view of the furnace 200 shown in FIG. 3. [Diagram 5] This is a diagram showing a heating curve conforming to ISO834-1:1999. [Figure 6] FIG. 1 shows an arrangement of insulating glass in which a Low-E glass 11a is arranged on the heated side and a fire-resistant glass 10a is arranged on the non-heated side. [Figure 7] FIG. 1 shows an arrangement of insulating glass 100 in which a Low-E glass 11a is arranged on the non-heated side and a fire-resistant glass 10a is arranged on the heated side. [Figure 8] FIG. 13 is a diagram showing a secondary sealing material according to a second embodiment and insulating glass to which the secondary sealing material is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.

[0012] [First embodiment] Fig. 1 is a diagram showing a secondary sealant and insulating glass according to a first embodiment of the present invention. In Fig. 1, insulating glass 100 includes a first glass 10, a second glass 11, a spacer 20, a desiccant 30, a hollow layer 40, a primary sealant 50, and a secondary sealant 60.

[0013] As shown in Fig. 1, in a double glazing 100, a first glass 10 and a second glass 11 are arranged opposite each other, and a spacer 20 is used to define the distance between the opposing first glass 10 and second glass 11 to form a hollow layer 40. A primary sealant 50 is provided between the first glass 10 and the spacer 20, and between the second glass 11 and the spacer 20. Note that the primary sealant 50 is illustrated as being thick for ease of understanding, but in reality it is extremely thin, and is set to a thickness that can be ignored as a whole compared to the thickness of the entire double glazing, for example, a thickness within a range of about 0.1 to 0.8 mm, and may be set to a thickness of about 0.3 mm, for example.

[0014] Furthermore, an adhesive may be used between the primary sealant 50 and the first glass 10 and second glass 11, if necessary, to form an adhesive layer.

[0015] A secondary sealant 60 is provided on the periphery of the insulating glass 100 so as to cover the outer periphery of the spacer 20 and the primary sealant 50. The secondary sealant 60 is provided so as to fill the space on the periphery between the first glass 10 and the second glass 11, and serves to seal the hollow layer 40. The desiccant 30 is provided to absorb moisture in the hollow layer 40 and keep it dry.

[0016] In this technical field, the sealant provided at the periphery of the insulating glass 100 so as to surround the outer peripheral surface of the spacer 20 is generally often called the "secondary sealant". That is, regardless of the presence or absence of the primary sealant, the sealant provided at the position surrounding the outer peripheral surface of the spacer 20 is often called the secondary sealant. Therefore, in this embodiment, regardless of the presence or absence of the primary sealant, the sealant provided so as to cover the outer peripheral surface (side surface) of the spacer 20 is referred to as the secondary sealant. In addition, when simply referring to the "sealant", both the primary sealant and the secondary sealant are included, but the primary sealant is provided between the spacer 20 and the first glass 10 and between the spacer 20 and the second glass 11, so it can be distinguished by its position.

[0017] FIG. 2 shows an embodiment of the first glass 10 using fire-resistant glass 10a, and the second glass 11 using Low-E glass 11a, and the insulating glass 100 is configured as fire-resistant insulating glass.

[0018] The Low-E glass 11a is a glass plate having a surface on the hollow layer 40 side coated with a low-emissivity Low-E metal film 16.

[0019] Fire-resistant glass 10a refers to glass plates that have a flame-resistance performance of 20 minutes or more as determined by a test method that conforms to the flame-resistance and semi-flame-resistance performance test evaluation method in the "Fire Resistance Performance Testing and Evaluation Procedure Manual (issued by the Building Materials Testing Center, established on June 1, 2000, last revised on July 13, 2020)". Examples of fire-resistant glass 10a include wire-reinforced glass, heat-resistant plate glass, and chemically strengthened glass.

[0020] Here, wired glass refers to wired plate glass as defined by JIS R3204 (wired plate glass and lined plate glass). Wired glass has a metal mesh inside the glass plate, and is configured to increase the strength of the glass. The mesh is, for example, arranged in a lattice pattern inside the wired glass.

[0021] Heat-resistant plate glass is glass that meets the "Heat-resistant Plate Glass Quality Standard" established by the Curtain Wall and Fire Openings Association. There are three types of heat-resistant plate glass: low-expansion fireproof glass, heat-resistant tempered glass, and heat-resistant crystallized glass.

[0022] Chemically strengthened glass is glass that has been strengthened by forming a compressive stress layer on the surface of the glass using a chemical strengthening method. Chemically strengthened glass is produced by immersing a glass plate, such as soda lime silicate glass containing Na and Li components, in a molten salt such as potassium nitrate, and replacing the Na ions and / or Li ions with small atomic diameters present on the surface of the glass plate with K ions with large atomic diameters present in the molten salt to form a compressive stress layer on the surface layer of the glass plate and increase its strength.

[0023] Chemically strengthened glass has better visibility and design than wired glass, and has a lower risk of thermal cracking. Chemically strengthened glass also has a lower risk of spontaneous breakage than heat-resistant strengthened glass, and can ensure strength and fire resistance even when made into a thin sheet. Furthermore, chemically strengthened glass can suppress warping more than heat-resistant strengthened glass, so when made into double-glazed glass, gaps in the sealant are less likely to open, and flames are less likely to leak from the periphery of the double-glazed glass in the event of a fire, improving fire resistance.

[0024] At least one of the main surfaces on which the compressive stress layer of the chemically strengthened glass is formed has a surface compressive stress value of preferably 300 MPa or more and 1000 MPa or less. If the surface compressive stress value is 300 MPa or more, the mechanical strength of the chemically strengthened glass is high. If the surface compressive stress value is 1000 MPa or less, the manufacturing cost can be reduced and the depth of the compressive stress layer can be ensured.

[0025] In at least one of the main surfaces on which the compressive stress layer of the chemically strengthened glass is formed, the thickness of the compressive stress layer in the plate thickness direction is preferably 20 μm or more and 50 μm or less. If the thickness of the compressive stress layer is 20 μm or more, sufficient strength against external forces can be obtained. If the thickness of the compressive stress layer in the plate thickness direction is 50 μm or less, immersion in the molten salt can be performed for a short period of time, and chemically strengthened glass can be easily obtained.

[0026] The thickness of the first glass 10 may be, for example, 3 mm or more and 11 mm or less, 6.8 mm or less, or 10 mm. The thickness of the second glass 11 may be, for example, 2.5 mm or more and 19 mm or less, 3 mm or more and 10 mm or less, or 5.0 mm. However, the thicknesses of the first glass 10 and the second glass 11 can be various depending on the application of the insulating glass 12.

[0027] The secondary sealant 60 according to this embodiment has excellent fireproofing performance and can be suitably used for fireproof insulating glass that combines fireproof glass 10a and Low-E glass 11a, but can also be used for insulating glass that has normal glass plates facing each other. Therefore, the secondary sealant 60 and the insulating glass 100 that uses it are not limited to fireproof insulating glass, but can also be applied to normal insulating glass.

[0028] First, before describing the secondary sealing material 60 according to this embodiment and the insulating glass 100 using the same, a fire test will be described. The fire test is a test that targets fire resistance tests based on ISO834-1:1999, and passing this test is an indicator of the fire resistance of the insulating glass.

[0029] Fig. 3 is a diagram for explaining a method of fire resistance testing based on ISO834-1:1999. As shown in Fig. 3, a burner 210 and a thermometer 220 are provided in a furnace 200, and the insulating glass 100 to be tested is attached to an opening 201 of the furnace 200. Fig. 4 is a front view of the furnace 200 shown in Fig. 3. For flame-blocking performance, in the state shown in Figs. 3 and 4, the insulating glass 100 is heated for 20 minutes according to a heating curve (T = 345 log10 (8t + 1) + 20, T: furnace temperature (°C), t: time (min)) conforming to ISO834.

[0030] Fig. 5 is a diagram showing a heating curve in accordance with ISO834-1: 1999. The inside of the furnace 200 is heated by the burner 210 so that the temperature inside the furnace measured by the thermometer 220 has a temperature gradient as shown in Fig. 5, and a fire resistance test of the insulating glass 100 is performed.

[0031] The fire resistance test is passed when the double-glazed glass 100 is able to withstand 20 minutes without flames penetrating the double-glazed glass 100 and without flaming on the non-heated side for 10 consecutive seconds. More precisely, the test is passed when all of the following conditions are met: no flames are emitted on the non-heated side for more than 10 seconds, no flames are emitted on the non-heated side for more than 10 seconds, and no damage or gaps such as cracks through which the flames can pass occur. For example, if the two panes 10 and 11 of the double-glazed glass 100 collapse, the flames will penetrate the double-glazed glass 100, and if the secondary sealant 60 and the spacer 20 burn and cracks or gaps through which the flames can pass occur, flames will occur from the four sides of the double-glazed glass 100. Therefore, the fire resistance of the secondary sealant 60 is the key to passing the fire resistance test. The fire resistance test is performed on both the front and back sides of the double-glazed glass 100.

[0032] 6 is a diagram showing the arrangement of a double-glazing unit 100 in which the Low-E glass 11a is arranged on the heated side and the fire-resistant glass 10a is arranged on the non-heated side. In this case, since the fire-resistant glass 10a is on the non-heated side, even if the Low-E glass 11a collapses, the fire-resistant glass 10a on the non-heated side will often survive and pass the test.

[0033] FIG. 7 is a diagram showing the arrangement of the double-glazing 100 in which the Low-E glass 11a of the double-glazing 100 is arranged on the non-heated side and the fire-resistant glass 10a is arranged on the heated side. In this case, the Low-E metal film 16 of the Low-E glass 11a reflects heat to the inside of the furnace 200, so the heating pace of the fire-resistant glass 10a is faster than that in the case of FIG. 6. If the inside of the secondary sealant 60 and the spacer 20 burns and the fire-resistant glass 10a collapses, the Low-E glass 11a is not as fire-resistant as the fire-resistant glass 10a, so the flame often penetrates. In other words, the arrangement pattern of FIG. 7 is likely to fail due to its configuration. In order to pass the fire resistance test with the arrangement of FIG. 7, it is required to increase the heat resistance of the secondary sealant 60 and prevent the fire-resistant glass 10a from collapsing as much as possible.

[0034] When a metal spacer, for example an aluminum spacer, is used as the spacer 20, even if the secondary sealant 60 burns, the spacer 20 can often prevent collapse. On the other hand, when the spacer 20 is made of resin or polyvinyl chloride, the spacer 20 cannot withstand the combustion of the secondary sealant 60, and the Low-E glass 11a often collapses.

[0035] Therefore, if the fire resistance of the secondary sealant 60 is improved, the spacer 20 can pass the fire resistance test regardless of the material of the spacer 20 .

[0036] Hereinafter, the secondary sealing material 60 capable of passing the fire resistance test based on ISO834-1:1999 and the insulating glass 100 using the same will be described in detail with reference again to FIG.

[0037] In FIG. 1, first, the spacer 20 may be either an aluminum spacer or a resin spacer.

[0038] Conventionally, double-glazing glass using aluminum spacers has been used, but in recent years, there has been an increasing need to improve the insulation around the glass, and so there is a growing need for resin spacers using vinyl chloride or other materials that have better insulation properties than aluminum spacers, and for spacers with desiccant kneaded in them (we will discuss desiccant kneaded spacers later).

[0039] As described above, when a resin spacer or a resin spacer containing a desiccant is used, the deterioration of fireproofing performance becomes an issue.

[0040] That is, since aluminum itself is a non-combustible material, the aluminum spacer can maintain its shape even after the fire resistance test.

[0041] On the other hand, resin spacers use hard resin materials such as PVC, so they melt, decompose, and burn during fire resistance tests, making it difficult to maintain their shape. Similarly, resin-incorporated spacers also have a resin matrix, so they melt, decompose, and burn during fire resistance tests, making it difficult to maintain their shape.

[0042] Generally, silicone-based sealants, polysulfide-based sealants, and hot-melt butyl-based sealants are used as secondary sealing materials.

[0043] Silicone sealants have high heat resistance but poor gas barrier performance, which raises concerns about the lifespan of insulating glass. Polysulfide sealants have high gas barrier properties but insufficient fire protection and generate acidic gases when burned. Hot-melt butyl sealants have very high gas barrier properties but insufficient fire protection.

[0044] The secondary sealant 60 according to this embodiment is a hot-melt butyl sealant, but is a sealant with significantly improved fireproofing performance. The secondary sealant 60 according to this embodiment ensures fireproofing performance even when the spacer 20 is a resin spacer or a desiccant-containing spacer, and constitutes a sealant with high durability for the insulating glass 100. The details of this will be described below.

[0045] The secondary sealing material 60 according to this embodiment contains a butyl-based rubber, a crystalline polyolefin, and an inorganic filler, in which the proportion of the butyl-based rubber relative to the total amount of the butyl-based rubber and the crystalline polyolefin is 98% by mass or more and 100% by mass or less, the proportion of the crystalline polyolefin is 0% by mass or more and less than 2% by mass (including cases where no crystalline polyolefin is included), and the proportion of the inorganic filler relative to 100 parts by mass of the total of the butyl-based rubber and the crystalline polyolefin is 100 parts by mass or more and 250 parts by mass or less.

[0046] The above-mentioned butyl rubbers include butyl rubber, halogenated butyl rubber, polyisobutylene, and partially vulcanized butyl. These are hot-melt butyl rubbers that can be molded by hot melt. Compared to silicone, they have the advantage of high moisture-proofing performance and a long life under normal use. There are also sealing materials made of polysulfide, but they contain sulfur components and may emit toxic gases when burned, so they are not suitable.

[0047] However, butyl-based rubber is fundamentally flammable, and it is difficult for it to pass a fire resistance test as is. However, in this embodiment, the above-mentioned compounding has significantly improved the fire resistance.

[0048] It is preferable that the butyl-based rubber is not cross-linked, because the non-cross-linked rubber has good fluidity as a secondary sealing material.

[0049] The proportion of the butyl rubber to the total amount of the butyl rubber and the crystalline polyolefin is 98% by mass or more, preferably 99% by mass or more, more preferably 99.5% by mass or more, and particularly preferably 100% by mass. The proportion of the butyl rubber to the total amount of the butyl rubber and the crystalline polyolefin is 100% by mass or less, and may be 99.9% by mass or less, 99.8% by mass or less, or 99.5% by mass or less.

[0050] The secondary sealant 60 according to the present embodiment contains polyisobutylene as a butyl-based rubber, and the proportion of polyisobutylene is preferably 5% by mass or more and 20% by mass or less. If the proportion of polyisobutylene is 5% by mass or more, the adhesion between the secondary sealant 60 and the first glass 10 and the second glass 11 is good. The proportion of polyisobutylene is more preferably 5% by mass or more, and particularly preferably 8% by mass or more. Furthermore, if the proportion of polyisobutylene is 20% by mass or less, the secondary sealant 60 is less likely to flow and has good shape retention. The proportion of polyisobutylene is more preferably 15% by mass or less, and particularly preferably 12% by mass or less.

[0051] The secondary seal material 60 according to the present embodiment may contain crystalline polyolefin together with the butyl rubber. The crystalline polyolefin refers to a homopolymer of an olefin such as ethylene or propylene, a copolymer with other monomers, or a modified product thereof, which has crystallinity. The polymer structure is preferably a syndiotactic structure or an isotactic structure, but may contain other structures. As the olefin, ethylene and propylene are particularly preferable.

[0052] Copolymers include copolymers of two or more olefins and copolymers of olefins and other monomers, and copolymers of ethylene or propylene and other monomers that do not inhibit crystallinity are suitable. Also, block copolymers are more suitable than alternating or random copolymers. Modified products include crystalline polyolefins with functional groups such as acid anhydride groups, carboxyl groups, and epoxy groups.

[0053] The crystalline polyolefin is effective in maintaining the shape of the insulating glass 100, and therefore contributes to improving the performance of the insulating glass 100 rather than improving the fireproofing performance.

[0054] In the above resin composition, the ratio of crystalline polyolefin to the total amount of butyl rubber and crystalline polyolefin is 0% by mass or more and less than 2% by mass. That is, crystalline polyolefin is not essential, and may be contained as a component as necessary. The ratio of crystalline polyolefin to the total amount of butyl rubber and crystalline polyolefin is preferably 1% by mass or less, more preferably 0.5% by mass or less, and particularly preferably does not contain crystalline polyolefin. In addition, when crystalline polyolefin is contained, the ratio of crystalline polyolefin to the total amount of butyl rubber and crystalline polyolefin may be 0.1% by mass or more, 0.2% by mass or more, or 0.5% by mass or more.

[0055] The secondary sealant 60 according to the present embodiment includes an inorganic filler. The ratio of the inorganic filler to the total of 100 parts by mass of the butyl rubber and the crystalline polyolefin is 100 parts by mass or more, preferably 150 parts by mass or more, and more preferably 180 parts by mass or more. The ratio of the inorganic filler to the total of 100 parts by mass of the butyl rubber and the crystalline polyolefin is 250 parts by mass or less, may be 230 parts by mass or less, or may be 220 parts by mass or less. Since the inorganic filler contains many components that leave residue even when burned, it contributes to improving the fireproof performance of the secondary sealant 60. Examples of the inorganic filler include talc, calcium carbonate, silica, magnesium hydroxide, carbon black, expanded black smoke, and adsorbents.

[0056] Talc, calcium carbonate and silica powder are used as fillers and contribute to maintaining the shape after combustion. These are non-combustible materials and help maintain the shape even after combustion, so it is preferable to mix them in a certain ratio. It is preferable to use talc or calcium carbonate rather than silica powder.

[0057] The particle size of the talc is, for example, preferably 3 μm or more and 10 μm or less, more preferably 4 μm or more and 8 μm or less, and even more preferably 4 μm or more and 6 μm or less, in terms of the median diameter d50.

[0058] Magnesium hydroxide and hydrated silica function as flame retardants, releasing moisture during combustion and suppressing combustion, i.e., they have the effect of cooling the combustion with water, which is useful for improving fire resistance.

[0059] Among carbon blacks, furnace-type carbon black has an adsorption effect equivalent to that of activated carbon, and has the effect of adsorbing oxygen and combustion gases and retarding combustion, thereby improving the fireproofing performance of the secondary sealing material 60. Carbon black has an extremely large nitrogen specific surface area, and has a large trapping effect on combustion gases such as methane and carbon monoxide.

[0060] Among carbon blacks, hard carbon type carbon black has a relatively large surface area, so it is preferable for fire prevention applications while increasing the strength of rubber. The nitrogen specific surface area of ​​carbon black is 50 m 2 / g or more 200m 2 / g or less, and 2 / g or more 150m 2 / g or less is more preferable, and 60m 2 / g or more 120m 2 / g or less. The hard carbon type carbon black is more preferably of HAF type.

[0061] The expandable graphite expands during combustion and contributes to maintaining the shape of the insulating glass. That is, the expandable graphite expands during combustion and plays a role in covering the burnt portion of the secondary sealant 60.

[0062] The adsorbent has the effect of adsorbing flammable gases and retarding combustion. Incidentally, flammable gases include, for example, methane and carbon monoxide. By adsorbing these flammable gases, it is possible to suppress combustion. Examples of the adsorbent include zeolite powder and silica gel. Incidentally, it is preferable to use zeolite in powder form.

[0063] In addition, it is preferable to use a pyrolysis promoter as an additive. Examples of pyrolysis promoters include organic sulfur compounds, more specifically, thioethers. Thioethers are materials that promote pyrolysis at 200-350°C, and they play a role in promoting pyrolysis at low temperatures and reducing combustion components at high temperatures.

[0064] It is not necessary to contain all of these inorganic filler components, and it is sufficient to contain at least one or more components. However, in order to improve fire retardancy, it is preferable to contain at least two of the above-mentioned inorganic filler components, more preferably to contain at least three, and even more preferably to contain at least four.

[0065] It is not necessary to use an adhesive, but if one is used, for example, a urethane adhesive made from polyolefin polyol, non-yellowing isocyanate, and a derivative of non-yellowing isocyanate may be used. These adhesives are non-melting cross-linking adhesives, and therefore have the property of remaining in place without melting even when heated, thereby improving the fire resistance of the insulating glass 100.

[0066] The secondary sealant preferably has a JIS A hardness of 50 or more and 90 or less at 25°C. This is a performance required of ordinary insulating glass 100 rather than a fireproof performance, and in order to maintain the shape of the insulating glass 100, the hardness is preferably 50 or more. In order to prevent cracking of the panes 10, 11 of the insulating glass 100, the hardness is preferably 90 or less. Furthermore, the secondary sealant 60 preferably has a JIS A hardness of 55 to 90 at 25°C.

[0067] According to the first embodiment, while a butyl-based sealant is used as the base material, an inorganic filler that improves fire resistance is added, thereby improving the fire resistance and enabling the construction of a secondary sealant 60 and a double-glazing material 100 that can pass the fire resistance test based on ISO834-1:1999.

[0068] Specifically, when the mass of the secondary sealant at room temperature is A and the mass when the secondary sealant is heated from room temperature in an air atmosphere at a rate of 10°C / min to 500°C is B, the mass ratio B / A can be set to 40% or more. The ratio of mass B to mass A can be considered as the residue rate of the secondary sealant 60 at 500°C when the secondary sealant 60 is heated at a rate of 10°C / min and gradually melts and loses its shape. According to the secondary sealant 60 of this embodiment, such a residue rate can be set to 40% or more, and fireproof performance can be improved.

[0069] [Second embodiment] FIG. 8 is a diagram showing a secondary sealing material and insulating glass according to the second embodiment.

[0070] The insulating glass 101 in the second embodiment differs from the insulating glass 100 in the first embodiment in that it has a desiccant-containing spacer 21 instead of the spacer 20. Other than that, it is the same as the insulating glass 100 in the first embodiment, and the first glass 10 and the second glass 11 have the same configuration as in the first embodiment and are therefore given the same reference numerals. Furthermore, the secondary sealant 61 is similar in material to the second sealant 60 in the first embodiment, but only the shape is different because the shape of the resin spacer 21 is different from that of the spacer 20.

[0071] The desiccant-containing spacer 21 is a type of spacer that has been widely used recently, and has a structure in which a desiccant 30 is mixed into the spacer. Since the desiccant-containing spacer is also a resin spacer, it has a lower fireproof performance than a metal spacer.

[0072] For such a desiccant-containing spacer 21, by applying the secondary sealing material 60 according to this embodiment, using fire-resistant glass 10a as the first glass 10 and Low-E glass 11a as the second glass 11, and making the double-glazing glass 100 into a fire-resistant double-glazing glass, it is possible to construct a double-glazing glass 101 that can pass the fire resistance test based on ISO834-1:1999.

[0073] In this manner, the secondary sealing material 60 according to this embodiment can be applied to various spacers 20, 21 and insulating glass 100, 101.

[0074] [Example] Hereinafter, an example will be described in which a double glazing 100 was constructed using the secondary sealing material 60 according to the first embodiment, and a fire resistance test based on ISO834-1:1999 was carried out.

[0075] In the following description, the same reference numerals as those used in the first embodiment will be used for the components to facilitate understanding.

[0076] In this embodiment, wired glass having a thickness of 6.8 mm was used as the first glass 10, Low-E glass having a thickness of 5 mm was used as the second glass 11, and the thickness of the hollow layer 40 was 12 mm. The width and height of the first glass 10 and the second glass 11 were 900 mm and 2000 mm, respectively.

[0077] The spacer 20 was made of a non-metallic material, and was made of a mixture of plastic and stainless steel, TGI (registered trademark)-Spacer M (manufactured by TECHNOFORM, Inc.) The height of the spacer 20 was 6.85 mm.

[0078] SM-488, a thermoplastic polyisobutylene-based sealing material manufactured by Yokohama Rubber Co., Ltd., was used as the primary sealing material 50. The thickness of the primary sealing material 50 was 0.3 mm on one side.

[0079] As shown in Table 1, the secondary sealant 60 was constructed by varying the ratio of the butyl rubber, the crystalline polyolefin, and the inorganic filler, and further varying the components contained in the inorganic filler.

[0080] The butyl rubber used was Butyl 365 manufactured by JSR. The polyisoprene used was Oppanol B15 manufactured by BASF. The polyethylene used was LJ902 manufactured by Japan Polyethylene. The talc used was FH104A manufactured by Fuji Talc. The calcium carbonate used was Whiten SB Red manufactured by Shiraishi Calcium Co., Ltd. The magnesium hydroxide used was Magseeds N manufactured by Konoshima Chemical Co., Ltd. The carbon black used was Seast 3 manufactured by Tokai Carbon Co., Ltd. The expanded graphite used was 955025L manufactured by Ito Graphite Co., Ltd. The adsorbent used was Molecular Sieve 4A powder manufactured by Union Showa Co., Ltd. The tackifier used was TRez HA125 manufactured by JXTG Corporation.

[0081] The insulating glass 100 was constructed under these conditions, and a fire resistance test based on ISO834-1: 1999 was carried out. The fire resistance test was carried out in the same manner as described with reference to Figs.

[0082] The results of the examples and comparative examples are shown in Table 1.

[0083] [Table 1] As shown in Table 1, among Examples 1 to 5, Examples 1 to 4 do not contain crystalline polyolefin, and have compositions containing only butyl rubber, inorganic filler, and additives. Example 5 contains 0.5 mass % of crystalline polyolefin.

[0084] In addition, in all of Examples 1 to 5, the proportion of inorganic filler relative to the total of 100 mass% of butyl rubber and crystalline polyolefin is 100 mass% or more. In addition, in Examples 1 to 5, the proportion of butyl rubber in the butyl rubber is 20 mass%, and the proportion of polyisobutylene is 10 mass%. As described above, with regard to crystalline polyolefin, Examples 1 to 4 are not included, but only Example 5 contains 0.5 mass% polyethylene.

[0085] As for the inorganic filler, Example 1 contains 30% by mass of talc, which is a non-combustible material, 10% by mass of carbon black, which functions as an adsorbent (activated carbon) for oxygen and combustion gases, and 20% by mass of zeolite 4A, which functions as an adsorbent for combustible gases. In addition, it contains 10% by mass of a tackifier as an additive.

[0086] In Example 2, the amount of talc in the inorganic filler was reduced from 30% by mass in Example 1 to 20% by mass, and 10% by mass of expanded graphite was added to make up for it.

[0087] Example 3 is based on Example 1, and has a composition in which calcium carbonate is used instead of talc as a non-flammable material at 10 mass%, and magnesium hydroxide is further added at 20 mass%, which functions as a flame retardant that releases water when burned.

[0088] Example 4 has the same component composition as Example 1, but the composition ratios are changed to 25 mass % talc, 25 mass % carbon black, and 10 mass % adsorbent.

[0089] Example 5 is based on Example 1, and the mass composition is also changed by subtracting 0.5 mass% of polyethylene as a crystalline polyolefin from the talc to make it 29.5 mass%, with 20 mass% carbon black, 15 mass% adsorbent, and 5 mass% adsorption aid.

[0090] On the other hand, as a comparative example, Comparative Example 1 is an example in which an existing hot melt butyl-based sealant is used, in which the ratio of inorganic filler to a total of 100 parts by mass of butyl-based rubber and crystalline polyolefin is 33 parts by mass, which is a different composition from Examples 1 to 5 in which the ratio is 100 parts by mass or more.

[0091] Comparative Example 2 has a composition similar to that of the examples described in WO 2018 / 199177. The proportion of the butyl rubber to the total amount of the butyl rubber and the crystalline polyolefin is 89.8% by mass, which is less than 98%, and is a composition smaller than those of Examples 1 to 5. In addition, the proportion of the inorganic filler to 100 parts by mass of the total of the butyl rubber and the crystalline polyolefin is 84 parts by mass, which is significantly smaller than the 100 parts by mass or more of Examples 1 to 5.

[0092] Comparative Examples 3 and 4 have the same compositions as Composition Examples 9 and 12 in Table 1 of Patent Document 1, respectively, and the ratio of inorganic filler to a total of 100 parts by mass of butyl-based rubber and crystalline polyolefin is 91 parts by mass, which is significantly smaller than the 100 parts by mass or more in Examples 1 to 5.

[0093] Examples 1 to 5 and Comparative Examples 1 to 4 were prepared with such compositions, and when a fire resistance test was carried out on Examples 1 to 5 and Comparative Examples 1 and 2, Examples 1 to 5 passed the test, while Comparative Examples 1 to 4 failed.

[0094] The 500°C combustion residue was evaluated as a more precise evaluation index than pass or fail of the test. The 500°C combustion residue was measured using a thermogravimetric analyzer (TA Instruments Thermogravimetric Analyzer Q50) by heating from room temperature to 900°C at a heating rate of 10°C / min in an air atmosphere, and the amount of residue at 500°C was determined. In Examples 1 to 5, all were around 60%, but in Comparative Examples 1 to 4, all were less than 40%, resulting in residues of 25% and 30%, respectively, less than half that of Examples 1 to 5.

[0095] These results show that the ratio of inorganic filler has a significant effect on the fire resistance of the secondary sealing material, and that by setting this ratio to 100 parts by mass or more, the fire resistance of the butyl rubber sealant can be significantly improved.

[0096] Considering Examples 1 to 5, Example 5 was the highest at 63%, followed by Example 1 at 60%, Example 2 at 59%, Example 4 at 58%, and Example 2 at 55%.

[0097] Although it is only a hypothesis, it is possible that the results of Example 5 suggest that the inclusion of a small amount of crystalline polyolefin may result in higher fire resistance, and the results of Example 2 suggest that increasing the amount of talc, a non-combustible material, may be more effective in improving fire resistance than the flame retardant effect of moisture generation from magnesium hydroxide.

[0098] In particular, the effects of polyethylene and talc, which are crystalline polyolefins, are higher than those of Comparative Example 1 by 5% in the 500°C combustion residues of Comparative Example 2, which contains polyethylene and talc, compared to Comparative Example 1, even when comparing the 500°C combustion residues of Comparative Examples 1 and 2. This suggests that they may have a greater impact than other components.

[0099] In this way, the secondary sealing material according to this embodiment can improve the fire resistance of double-glazed glass, even when a resin spacer or a resin spacer containing a desiccant is used in the double-glazed glass, and can leave a large residue even when exposed to flame radiation, allowing the glass to pass the fire resistance test based on ISO834-1:1999.

[0100] In addition, the JIS A hardness was measured at 25° C. The JIS A hardness was measured in accordance with JIS K7215 using a type A hardness tester (GS-619RG, manufactured by Techclock Corporation) to measure the value immediately after pressure application.

[0101] Although the preferred embodiments and examples of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments and examples, and various modifications and substitutions can be made to the above-described examples without departing from the scope of the present invention.

[0102] For example, in the double-glazing glass of Examples 1 to 5, if chemically strengthened glass is used instead of the wire-reinforced glass, or if low-expansion fireproof glass, heat-resistant strengthened glass, or heat-resistant crystallized glass certified as heat-resistant plate glass by the Architectural Openings Association is used, the double-glazing glass can similarly pass the fire resistance test. [Explanation of symbols]

[0103] 10 First Glass 10a Fire-retardant glass 11 The Second Glass 11a Low-E glass 20, 21 Spacer 30 Desiccant 40 hollow layer 50 Primary sealing material 60 Secondary sealing material 100, 101 Double glazing

Claims

1. A sealing material for sealing the peripheral portion of a double-glazing unit in which two or more glass sheets are arranged opposite each other and spaced apart via a spacer so as to form a hollow layer therebetween, The sealing material has a butyl-based rubber and an inorganic filler, and the proportion of the butyl-based rubber relative to the total amount of the butyl-based rubber and the crystalline polyolefin is 98% by mass or more and 100% by mass or less, and the proportion of the crystalline polyolefin is 0% by mass or more and less than 2% by mass (including the case where the crystalline polyolefin is not included), The ratio of the inorganic filler to 100 parts by mass of the total of the butyl-based rubber and the crystalline polyolefin is 100 parts by mass or more and 250 parts by mass or less, The butyl-based rubber includes polyisobutylene, The sealing material has a polyisobutylene content of 5% by mass or more and 20% by mass or less. Sealing material.

2. The sealant was used as a secondary sealant for a double-glazed glass having a first glass and a second glass disposed opposite each other, the double-glazed glass was attached to the opening of a furnace, and the peripheral portion of the double-glazed glass was sealed with the sealant. The first glass was a wire-reinforced glass having a thickness of 6.8 mm and having fire resistance, and the second glass was a Low-E glass having a thickness of 5 mm. The sealant had a thickness of 12 mm, and the width and height of the first glass and the second glass were 900 mm and 2000 mm, respectively. A burner was disposed opposite the first glass. A heating curve conforming to ISO834-1:1999 (T = 345 log10 (8t + 1) + 20, T: furnace temperature (°C), t:

2. The sealing material according to claim 1, wherein, when the double-glazing material is heated for 20 minutes in accordance with a test time (min) in accordance with ISO 834-1:1999, a flame from the burner does not penetrate the double-glazing material, and a state in which no flame is generated for 10 consecutive seconds is maintained for 20 minutes.

3. 3. The sealing material according to claim 1, wherein the ratio B / A of the mass A of the sealing material at room temperature to the mass B of the sealing material when heated from room temperature to 500° C. at a rate of 10° C. / min in an air atmosphere is 40% or more.

4. The sealing material according to any one of claims 1 to 3, wherein the butyl-based rubber is not crosslinked.

5. The sealing material according to claim 1 , wherein the inorganic filler contains an adsorbent.

6. The sealing material according to any one of claims 1 to 5, wherein the inorganic filler contains carbon black.

7. The sealing material according to any one of claims 1 to 6, having a JIS A hardness of 55 to 90 at 25°C.

8. The sealing material according to claim 1, further comprising a thermal decomposition promoter as an additive.

9. Two glass plates arranged opposite each other; a spacer provided between the two glass plates and defining a distance between the two glass plates; and the sealant according to any one of claims 1 to 8, surrounding an outer periphery of the spacer and sealing a space formed by the spacer and the two glass plates.

10. The insulating glass according to claim 9, wherein one of the two glass plates is a fire-resistant glass and the other is a Low-E glass.

11. The insulating glass according to claim 9 or 10, further comprising a second sealant between the spacer and the two glass plates, the second sealant having a composition different from that of the sealant.

Citation Information

Patent Citations

  • Butyl hot melt adhesive and preparation method thereof

    CN105385388A

  • Sealant composition

    JP1998110072A

  • Plural-layer glass

    JP1998114551A

  • Resin composition

    JP2007211195A

  • Fire protection double-glazed glass

    JP2013136473A